Lived Institutions as History of Experience
XVII, 353 p. 14 illus.
Keywords: This open access book focuses on institutions that were produced and formed by the emerging welfare state. How were institutions experienced by the people who interacted with them? How did institutions as sites of experience shape and structure people’s everyday lives? Histories of institutions have mainly focused on the structures and power relations produced by institutional settings. Likewise, despite an extensive historiography of the welfare state, reflections on individuals’ experiences of welfare are few. By using ‘lived institutions’ as its conceptual frame, this edited collection merges the fields of institutional studies, the history of the welfare state – and the novel and vibrant field of the history of experience. Johanna Annola is Associate Professor of Social History and Academy Research Fellow at the Academy of Finland Centre of Excellence in the History of Experiences, Tampere University, Finland. Hanna Lindberg is Research Fellow at Åbo Akademi University and Tampere University, Finland. Pirjo Markkola is Professor of History at Tampere University, Finland and the Director of the Academy of Finland Centre of Excellence in the History of Experiences.